PENDIDIKAN KARAKTER SYAIKH ABDUL QODIR AL-JAILAANII (STUDI KITAB AL FAIDUR ROHMAANII BAB VI DAN VII) - Fathurrahman, F; Jianto, Afiudis Juni Fais; Umniyyah, Inas (Al’ulum Jurnal Pendidikan Islam, 2025)
Character education plays a crucial role in shaping an individual's personality to develop good morals. In Islam, character education is based on the values of faith, piety, and noble morals. One of the influential figures in character education is Syaikh Abdul Qadir al-Jailaanii, a scholar and Sufi known for his piety and teachings that emphasize heart purification and obedience to Allah. The research employs a library research method, using an analytical approach to explore the concepts and thoughts of the figure. The primary source of this study is Kitab Al Faidur Rohmaani, while supporting sources include books, journals, and previous relevant studies. The findings of this research indicate that the teachings and exemplary life of Syaikh Abdul Qadir al-Jailaanii, as documented in his manakib, emphasize the importance of character values such as sincerity, patience, humility, exemplary behavior, discipline, and reliance on Allah (tawakkal). The character education exemplified in his life is not merely theoretical but is manifested in real attitudes and actions, such as maintaining a strong relationship with Allah, demonstrating noble character toward others, and consistently practicing religious devotion (istiqamah). This study concludes that the character education portrayed in Kitab Al Faidur Rohmaani remains highly relevant today. The teachings and exemplary life of Syaikh Abdul Qadir al-Jailaanii can serve as an inspiration in character development, particularly in the field of Islamic education.